Demografik dönüşüm sürecinde yaşlılara yönelik uygulanan sosyal yardım ve hizmetler: Güney Avrupa ve Türkiye mukayesesi - Keten, Abdüssamed (My University, 2017)
Demografik dönüşüm, hem dünyada hem de Türkiye’de gün geçtikçe tartışılanbir konu haline gelmiştir. ABSTRACT The demographic transformation was discussed lasting for long time in bothTurkey and throughout the world. If the population structure of the countries isconsidered to have undergone serious changes in the last 50 years, the prospect of oldage and aging will undoubtedly come to the forefront.
Keywords: ageing; Demografik dönüşüm; Devlet politikası; Güney Avrupa; refah devleti; social assistance; social policy; socialwork; sosyal hizmet; sosyal politika; Sosyal yardım; Toplumsal hizmetler; Türkiye; welfare state; yaşlanma Demographic change; Yaşlılar